Management of ophthalmic surgical instruments and processes optimization: mixed method study - Daniela Silva dos Santos Schneider; Ana Maria Müller de Magalhães; Cecilia Helena Glanzner; Elisabeth Gomes da Rocha Thomé; João Lucas Campos de Oliveira; Michel José Anzanello (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Aim: Analysis of the use of ophthalmic instruments during surgical procedures in order to propose a material management method. Method: Mixed method study, sequential exploratory design, performed from January to June 2015, at a university hospital in southern Brazil. First, a qualitative approach was held from brainstorming and field observation. Themes were grouped into thematic categories. By connection, the quantitative stage happened through matrix arrangement and linear programming, culminating in the instrument management proposal. Results: Given categories - instruments reorganization according to the time of the surgical procedure and the need surgical instruments for in each procedure - guided the definition of existing restrictions and application of mathematical models. There was an average reduction of 13.10% in the number of surgical instruments per tray and an increase of 17.88% in surgical production. Final considerations: This proposal allowed the rationalization and optimization of ophthalmic instruments, favoring sustainability of the organization.